Effect of Two Different Injection Techniques of Local Anaesthetic in Ultrasound Guided Supraclavicular Brachial Plexus Block on Diaphragmatic Motility - Prasad, Jagat Narayan; Ghimire, Ashish; Chaudhary, Pashupati; Guddy, KM; Sarraf, Deependra Prasad (Journal of BP Koirala Institute of Health Sciences, 2024)
Background: Deposition of local anesthetic (LA) caudal and posterolateral to brachial plexus might result in less hemidaiphragmatic paralysis. Objective was to compare the effect of two different injection techniques of 0.5% Ropivacaine in ultrasound guided supraclavicular brachial plexus block (BPB) on diaphragmatic motility.Methods: A prospective randomized double-blinded comparative study was conducted among adults undergoing right upper limb surgery. In group A (n = 17), 20 mL 0.5% ropivacaine was injected caudal and posterolateral to the brachial plexus. In group B (n = 17), two aliquots each of 10 mL ropivacaine were injected at two separate locations within the plexus sheath. Diaphragmatic excursion and success of blockade were measured at 15 and 30 minutes.Results: All patients in group B had sensory and motor blockade in both median and musculocutaneous nerve territories at 15 minutes while it was only in 10 patients (58.82%) in median nerve territory and 7 patients (41.18%) in musculocutaneous nerve territory in group A (P-value< 0.05). At 30 minutes, 17 (100%) patients in group B and 16 (94.12%) patients in group A had successful blockade (p-value>0.05). At 15 minutes, complete hemidiaphragmatic paralysis was seen in 10 (58.82%) patients in group B and three (17.65%) patients in group A (p-value